Batas Konsumsi Berbasis Kapasitas Finansial dalam Tafsir al-Mishbah: Utang Konsumtif dalam Perspektif Al-Qur’an - Nurul Huda; Sugeng Wanto; Aplirinda M Harahap (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
Debt-financed consumption becomes a problem when expenditure is not commensurate with financial capacity and the proportionality of asset management. The problem is not simply the existence of debt, but its use to finance consumption that may exceed one’s ability to meet obligations; therefore, the Qur’anic perspective through Tafsir al-Mishbah is relevant for formulating contextual ethical limits on consumption. This study aims to analyze the limits of consumption, position financial capacity as an ethical parameter, and identify the parameters of consumptive debt limits from a Qur’anic perspective. This study uses a qualitative, literature-based approach through thematic interpretation (mawḍūʻī) with an analytical-contextual orientation, using the Qur’an and Tafsir al-Mishbah as primary sources and literature on interpretation, Qur’anic studies, Islamic economic ethics, consumption, and consumptive debt as secondary sources. The analysis inventories verses, traces interpretations, identifies concepts, and maps relationships between concepts. The results show that consumption limits are established through proportionality, balanced expenditure, avoidance of isrāf and tabżīr, and responsible asset management. Financial capacity becomes an ethical parameter because purchasing power is not the same as the ability to bear the consequences of consumption. Consumptive debt becomes problematic when consumption exceeds needs and capabilities, especially when it disrupts basic needs, proportionality of expenditure, and transaction responsibility. Consumptive debt limits are determined by integrating needs, financial capacity, protection of basic needs, proportionality, and responsibility. These findings broaden the reading of Qur’anic consumption ethics toward aligning consumption with financial capacity and obligations, while strengthening the understanding of consumptive debt as an ethical issue of asset management.